Typology of sociotechnical transition pathways - and Geels, Frank W.; Schot, Johan (Research Policy)
Contributing to debates about transitions and system changes, this article has two aims. First, it uses criticisms on the multi-level perspective as stepping stones for further conceptual refinements. Second, it develops a typology of four transition pathways: transformation, reconfiguration, technological substitution, and de-alignment and re-alignment. These pathways differ in combinations of timing and nature of multi-level interactions. They are illustrated with historical examples.